Dielectric and energy storage properties of Mn-doped Ba0.3Sr0.475 La0.12Ce0.03TiO3 dielectric ceramics. Issue 1 (January 2017) - Ye, X.Y.; Li, Y.M.; Bian, J.J.
Abstract: Microstructure, temperature and frequency dependent dielectric and energy storage properties of Ba0.3 Sr0.475 La0.12 Ce0.03 Ti1−x Mnx O3 (x = 0 − 0.005) have been investigated with X-ray diffractometer, and scanning electron microscope, broad band dielectric spectrometer and ferroelectric analyzer. The doping of Mn substantially decreased the dielectric loss, but made some of Ce 3+ be oxidized to Ce 4+ entering into B-site, which resulted in the formation secondary phases. For the Mn-doped composition, extremely low dielectric loss (10 −5 order of magnitude at 10 kHz) could be obtained at room temperature. The relaxation mechanism at low temperature is of the dipole type for the undoped composition and that at high temperature (>500 K) is governed by the trap controlled ac conduction, respectively. The energy storage properties were improved by the doping with Mn due to the increase of insulation. Maximum energy density of 0.953 J/cm 3 could be obtained for x = 0.003 composition with the BDS of 247 kV/cm and efficiency of 93%.